The Cham Minority Group Cambodia Division Within Introduction to Comtemporary Changes in Cham Communiries Cham Jahed in Mosque for Friday Prayer - Seise, Claudia (Religi: Jurnal Studi Agama-agama, 2007)
The Cham forms an ethnic minority group, both in Vietnam and Cambodia. In  my  research  paper  I  will focus  on the  Cham  in  Cambodia, who emigrated from  their  lost  homeland -the Champa Kingdom in present day Vietnam. The Cham in Cambodia number around 200,000 people and make up two percent of  the  country's population.